PBC approach applied on a DC-DC step-down converter for providing service to CPLs (2019)
This paper addresses the problem of output voltage regulation for step-down converters (buck converters) for constant power load (CPL) applications. The model of the CPL corresponds to a hyperbolic constraint that introduces nonlinearities on the dynamical model. To regulate the voltage profile in this nonlinear load a passivity-based control (PBC) approach is proposed. The main advantage of the proposed control approach corresponds to the parametric independence of the controller, even if the CPL and the asymptotic stability in the sense of Lyapunov are unknown. Numerical results validate the proposed control approach in comparison to conventional PID controller. © 2019 IEEE.